Gasto federal com crianças e adolescentes: 1994 a 1997 - Ana Maria Resende de Chagas; Frederico Augusto Barbosa da Silva; Paulo Roberto Corbucci (Instituto de Pesquisa Econômica Aplicada (IPEA), 2001)
– This text synthesizes a previous study whose objective was to analyze Federal expenditures with children and adolescents (those aged 0 to 18) in the 1994 - 1997 period. Federal expenditures are analyzed through budget information, considering thus the values actually spent during the period. Two methodologies were used: one is to classify expenditures according to areas of action - which we use to calculate social expenditure indices - and the other in which expenditures are classified according institution. Under this last prism, these Ministries are analyzed: education, health, social assistance, justice, and social security. Expenditures with children and adolescents is identified by the objective of each individual expenditure up to the level of subprogram or even project/ activity. Total and 'per capita' expenditures with children and adolescents are estimated and the most important programs in each area are detailed. In order to analyze the behavior of global federal social expenditures, we calculated the following indices: (i) the Public Expenditure Index (IGP), (ii) the Social Allocation Index (IAS), (iii) the Social Priority Index (IPS), and (iv) the Human Expenditure Index (IGH). Except for the Social Allocation Index, all others exhibited negative growth during the period. In other words, there was more commitment in federal expenditures with social programs, but the share to priority action diminished. The analysis of the data allowed us to identify important changes in the amount and composition of resources allocated to children and adolescents during the 1994-1997 period. In all the years we analyzed, health accounted for the largest share of resources and its weight grew throughout the period. In 1994, 36% of resources were destined to education, 56.3% to health, and 7.7% to social assistance; in 1997, the values were, 22.3%, 68.7%, and 9%, respectively. Education suffered a continuous reduction in its share of expenditures. The result was a reduction of 35% in absolute values between the beginning and the end of the period. Social assistance oscillated around a positive trend, with a 23.3% increase between 1994 and 1997.
Keywords: 330